Application of SWOT Analysis to Determine Strategic Position of PT XYZ in National Market - Nada Salsabila Aglifianti; Hapzi Ali (Siber Nusantara Review, 2025)
This study aims to analyze the application of SWOT analysis in determining the strategic position of PT XYZ in the Indonesian national market. The object of the study is PT XYZ, a company that faces challenges and opportunities in domestic market competition. This research method uses SWOT analysis (strengths, weaknesses, opportunities, and threats) to identify internal (strengths and weaknesses) and external (opportunities and threats) components that can affect business performance. The results of the study indicate that PT XYZ has strengths such as continuous product innovation, extensive distribution networks, and strong brand reputation. However, the company also faces problems such as dependence on the local market and slow digital adoption. While threats include intense competition and fluctuations in raw material prices, opportunities that can be utilized include the development of e-commerce, government support, and the possibility of expansion into the ASEAN market. To maintain PT XYZ's strategic position in the national market, strategies such as improving digital platforms, increasing operational efficiency, and developing new products are formulated based on SWOT analysis.